Actinomycetoma distal radius mimic osteosarcoma: A case report of a rare presentation - Hassan Elbahri; Adnan Ayman Mohammed Adnan Alnaser; Sawsan A. M. Babiker; Alaa Hatim Ameer Mohamed (Clinical Case Reports, 2023)
Key Clinical Message Actinmomycetma is a granulomatous infection with a presentation was very similar to osteosarccoma. Multidisciplinary team and triple assessments are extremely important to prevent misdiagnosis, surgical treatment in combination with medical treatment followed by regular clinical and radiological follow‐up can be a limb‐saving procedure in such cases. Abstract Various conditions may mimic osteosarcoma. The differential diagnosis of osteosarcoma is broad; Includes tumors, infection, trauma, and inflammatory processes arising from the musculoskeletal system. A proper history, examination, diagnostic imaging studies, and pathological analysis are essential to establish a precise diagnosis. This case report serves to illustrate the significance of recognizing the similarities between these two lesions and other rare features that will help to differentiate between actinomycetoma and osteosarcoma, to prevent late or misdiagnosis.